Tinjauan Literasi Keuangan Bagi Santri Pondok Pesantren Madura: Studi Kasus Pondok Pesantren Syaichona Kholil Kabupaten Bangkalan - Galuh Widitya Qomaro; Aldila Septiana (JES (Jurnal Ekonomi Syariah), 2017)
Need priority scale arrangement is done to avoid the behavior of irrational consumption. It also must pay attention to the financial capabilities to avoid greater expenditure than income. Therefore, to make the right economic decisions in consuming and avoid luxurious lifestyle, it is necessary for us understanding financial literacy. Financial Literacy is knowledge to manage finance. One of the intelligences that must be possessed by modern men is financial intelligence, namely the intelligence in managing personal assets, especially in managing personal financial assets. The object of research in this paper is students at traditional Muslim School at traditional Muslim at school of Syaichona Kholil Bangkalan District, where students at traditional Muslim School are students who live far apart from parents equipped with knowledge in managing finances and allowance. Are the students at traditional Muslim School able to coordinate his finances in traditional Muslim School? Based on the result of the research, it can be described as follows: the concept of someone's financial literacy can be seen from the his/her cognitive process or knowledge which he has in managing finance, and his/her attitudes toward personal finance that will affect his financial behavior or decision in managing finance. From the existing theory, it is adapted based on basic knowledge as well as financial attitudes for teenagers with age of 13-18 years. A review of financial literacy for students at traditional Muslim School of  Syaichona Kholil Bangkalan District is appraised by simplicity and mutual sharing among fellow who is able to maintain an individual life as a social creature in the environmental diversity of the community. This sense of solidarity and kinship is needed to bring students at traditional Muslim School into real life after they no longer live in traditional Muslim School of Syaichona Kholil Bangkalan Regency. Keywords: Financial Literacy, Traditional Muslim School, Syaichona Kholil